2011
DOI: 10.1186/1471-2407-11-231
|View full text |Cite
|
Sign up to set email alerts
|

GP88 (PC-Cell Derived Growth Factor, progranulin) stimulates proliferation and confers letrozole resistance to aromatase overexpressing breast cancer cells

Abstract: BackgroundAromatase inhibitors (AI) that inhibit breast cancer cell growth by blocking estrogen synthesis have become the treatment of choice for post-menopausal women with estrogen receptor positive (ER+) breast cancer. However, some patients display de novo or acquired resistance to AI. Interactions between estrogen and growth factor signaling pathways have been identified in estrogen-responsive cells as one possible reason for acquisition of resistance. Our laboratory has characterized an autocrine growth f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 40 publications
0
37
0
Order By: Relevance
“…Moreover, PGRN treatment in MCF-7 cells inhibited the tamoxifen-induced down-regulation of bcl-2 [94]. PGRN may in addition interfere with aromatase therapy since PGRN inhibited the efficacy of the aromatase inhibitor letrozole in a human breast cancer cell line [95]. PGRN expression level was significantly increased in letrozole resistant tumor cells compared with letrozole sensitive cancer cells [95].…”
Section: Pgrn Cell Survival and Drug Resistancementioning
confidence: 84%
See 1 more Smart Citation
“…Moreover, PGRN treatment in MCF-7 cells inhibited the tamoxifen-induced down-regulation of bcl-2 [94]. PGRN may in addition interfere with aromatase therapy since PGRN inhibited the efficacy of the aromatase inhibitor letrozole in a human breast cancer cell line [95]. PGRN expression level was significantly increased in letrozole resistant tumor cells compared with letrozole sensitive cancer cells [95].…”
Section: Pgrn Cell Survival and Drug Resistancementioning
confidence: 84%
“…PGRN may in addition interfere with aromatase therapy since PGRN inhibited the efficacy of the aromatase inhibitor letrozole in a human breast cancer cell line [95]. PGRN expression level was significantly increased in letrozole resistant tumor cells compared with letrozole sensitive cancer cells [95]. Other hormone-based therapies may also be sensitive to PGRN production.…”
Section: Pgrn Cell Survival and Drug Resistancementioning
confidence: 99%
“…The combination treatment also disturbed the balance between proapoptotic (Bax) and antiapoptotic (Bcl-2) members through the inhibition of Bcl-2. Other research groups have reported that GEP overexpression led to the development of tamoxifen and letrozole resistance through the protection of Bcl-2 in breast cancers (36,37). The roles of Akt-PKB and MEK-ERK in apoptosis induced by cytotoxic drugs, and the interactions between the Akt-PKB pathways and Bcl-2 family members in the regulation of apoptosis have been described extensively (38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we have shown that GP88 confers resistance to the aromatase inhibitor letrozole in aromatase overexpressing cells MCF7-CA and AC1 cells while estrogen receptor expression remained unchanged [32]. Naturally letrozole resistant cells LTLT and AC1LTR cells overexpressed GP88 whereas inhibition of GP88 by SiRNA restored letrozole responsiveness [32]. Pathological studies with paraffin embedded breast cancer biopsies have shown positive GP88 tissue expression in 60% of ductal carcinoma in situ (DCIS) and 80% of invasive ductal carcinoma (IDC) whereas normal mammary epithelium and benign tumors were GP88 negative [33] In IDC, GP88 expression correlated with parameters of poor prognosis such as tumor grade, proliferation index and p53 expression.…”
Section: Introductionmentioning
confidence: 93%
“…In addition, we have shown that GP88 confers resistance to the aromatase inhibitor letrozole in aromatase overexpressing cells MCF7-CA and AC1 cells while estrogen receptor expression remained unchanged [32]. Naturally letrozole resistant cells LTLT and AC1LTR cells overexpressed GP88 whereas inhibition of GP88 by SiRNA restored letrozole responsiveness [32].…”
Section: Introductionmentioning
confidence: 96%